In defence of Soft OR: Reflections on teaching Soft OR. Issue 1 (2nd January 2020) - Ackermann, Fran; Alexander, James; Stephens, Ashley; Pincombe, Brandon
Abstract: Soft Operational Research (OR) methods, despite providing considerable benefit to organisations in tackling a range of problems, are not widely utilised by OR practitioners. Reasons include a lack of awareness of both methods and their benefits, perceptions that the methods lack the robustness of their "Hard" OR cousins and challenges in learning the methods. The research presented in this article seeks to better understand these issues and their implications for teaching Soft OR through (a) the development and delivery of a pedagogically informed bespoke training program in the Soft OR method Strategic Options Development and Analysis to analysts working in a Defence environment and (b) reflecting upon the training through analysis of learning diaries and trainee feedback. The findings contrast the challenges faced by post-experience and undergraduate students in learning Soft OR methods, and encompass (i) tailoring programs to match students' experience, (ii) appreciating the significance of context in the adoption of Soft OR approaches, and (iii) identifying mechanisms for gaining competence and confidence in these approaches. The research aims to improve uptake of Soft OR methods, addresses a literature gap on the challenges of Soft OR from a learner perspective, and extends research in this area into the Defence domain.